TECHNOLOGY OF COMMERCIAL WEB-RESOURCE MANAGEMENT BASED ON FUZZY LOGIC - Alieksieieva, K. A.; Berko, A. Y.; Vysotska, V. A. (Radio Electronics, Computer Science, Control, 2015)
The method of content management as its life cycle stage in electronic content commerce systems based on Fuzzy Logic is proposed. The method of content management describes the commercial web resources forming in electronic content commerce systems and automation technology that simplifies the content management. The main problems of electronic content commerce and functional services of content management are analyzed. The proposed method gives an opportunity to create an instrument of web resources processing and to implement the subsystem of content management. Tasks of content management are: operational and retrospective database formation and rotation; the user experience personalization; personal user queries and sources storing; operation statistics analysis; search providing in database; initial forms generation on information resources; information interaction with other databases; Web resource formation and processing. Content management subsystem is implemented through its caching (generates a page once; then it is several times faster loaded from the cache, which is updated automatically after a certain period of time or when making changes to specific sections of an Web resource, or by administrator command) or information blocks formation (blocks conservation in the Web resources editing stage and page collection from these blocks at the user request its).